Analisa Sistem Proteksi Petir Pada Sutet 275 KV Menggunakan Software ATP-EMTP - Bella Novita Dona; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia has high humidity intensity. This causes the lightning strike density on Indonesia be high too. Lightning strikes can damage electrical equipment and transmission networks, especially 275 kV Air Line of Extra High Voltage (SUTET), because it has a high towers that is susceptible to lightning strikes. Therefore, lightning protection with arrester is needed. This study, will examine the influence of installation variations of arrester based on classification towers at T1,T3,T5,T7,T9, and T2,T4,T6,T8,T10, variations in stroke current (10 kA, 30 kA, 60 kA, and 100 kA), and variations in lightning strike position (T1, T5, and T10) by using ATP-EMTP software. The analysis process is done by modeling all parameters of the transmission line and power plant. The results of this study are if lightning strikes a particular towers, the voltage on the towers will be higher than the other towers, the greater lightning impulse current, the greater the voltage that appears on its phase voltage; and so the arresters used for this conditions at T2, T4,T4, T8, and T10 are more efficient in terms of reducing the voltage.Keywords : lightning arrester , extra high voltage, surge arrester, drop voltage, ATP